Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/molecules22050814
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of EPS Production and Characterization by a Halophilic Bacterium, Kocuria rosea ZJUQH from Chaka Salt Lake with Response Surface Methodology

Abstract: With the rising awareness of microbial exopolysaccharides (EPSs) application in various fields, halophilic microorganisms which produce EPSs have received broad attention. A newly identified Kocuria rosea ZJUQH CCTCC M2016754 was determined to be a moderate halobacterium on account of its successful adaption to the environment containing 10% NaCl. The optimal combination of fermentation medium compositions on EPS production was studied. In this work, a fractional factorial design was adopted to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…No absorption peaks around the region of 1700–1770 cm −1 attributed to C=O stretching of carbonyls in esters were observed (Kielak et al, 2017). The peak in the region of 1644 cm −1 would represent the absorption band of carboxylic groups, suggesting the presence of acidic sugars (Deshmukh et al, 2017; Kielak et al, 2017), and similarly, the peak at 1219 cm −1 observed in some samples could be attributed to C‐O stretching in ether or alcohol groups (Gu et al, 2017; Kanamarlapudi & Muddada, 2017). The peak at 1051 cm −1 indicates a possible α (1→6) glucosidic bond with certain flexibility (Gu et al, 2017), while the absorption band at 978 cm −1 suggests the vibrations of the glycosidic bonds C‐O‐C and the peak in the region of 840–860 cm ‐1 are characteristic of α‐D‐glucan (Kanamarlapudi & Muddada, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No absorption peaks around the region of 1700–1770 cm −1 attributed to C=O stretching of carbonyls in esters were observed (Kielak et al, 2017). The peak in the region of 1644 cm −1 would represent the absorption band of carboxylic groups, suggesting the presence of acidic sugars (Deshmukh et al, 2017; Kielak et al, 2017), and similarly, the peak at 1219 cm −1 observed in some samples could be attributed to C‐O stretching in ether or alcohol groups (Gu et al, 2017; Kanamarlapudi & Muddada, 2017). The peak at 1051 cm −1 indicates a possible α (1→6) glucosidic bond with certain flexibility (Gu et al, 2017), while the absorption band at 978 cm −1 suggests the vibrations of the glycosidic bonds C‐O‐C and the peak in the region of 840–860 cm ‐1 are characteristic of α‐D‐glucan (Kanamarlapudi & Muddada, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…to C-O stretching in ether or alcohol groups (Gu et al, 2017;Kanamarlapudi & Muddada, 2017). The peak at 1051 cm −1 indicates a possible α (1→6) glucosidic bond with certain flexibility (Gu et al, 2017), while the absorption band at 978 cm −1 suggests the vibrations of the glycosidic bonds C-O-C and the peak in the region of 840-860 cm -1 are characteristic of α-D-glucan (Kanamarlapudi & Muddada, 2017). The band at 630 cm -1 is due to the out-of-plane bending of -OH groups (Deshmukh et al, 2017).…”
Section: F I G U R Ementioning
confidence: 99%
“…This latter is a halophilic bacterium able to produce a polysaccharide designated as Kocuran [49]. Recent publications claims that certain strains of Kocuria rosea have great potential to be exploited as a source of EPSs utilized in industry, as well as in the biotreatment of hypersaline environments [50]. In addition, the genus Brachybacterium was detected in the isolates of sample 1A with a 100% rate of similarity, represented by the species Brachybacterium rhamnosum.…”
Section: Discussionmentioning
confidence: 99%
“…Six different fermentation media were used as follows: (1) The yeast peptone dextrose adenine (YPDA) medium: yeast extract 10 g, peptone 20 g, glucose 20 g, and distilled water 1 L [ 15 ]; (2) Czapek medium: sucrose 30 g, sodium nitrate 3 g, dipotassium phosphate 1 g, potassium chloride 0.5 g, magnesium sulfate 0.5 g, ferrous sulfate 0.01 g, and distilled water 1 L [ 16 ]; (3) Medium 1: sucrose 50 g, soybean peptone 40 g, yeast extract 30 g, glycerin 16 g, and distilled water 1 L [ 17 ]; (4) Medium 2: sucrose 50 g, glucose 20 g, yeast extract 50 g, ammonium sulfate 10 g, potassium dihydrogen sulfate 3 g, glycerol 2 g, calcium chloride 1 g, and distilled water 1 L [ 18 ]; (5) Medium 3: sucrose 60 g, yeast paste 40 g, ammonium sulfate 10 g, potassium dihydrogen sulfate 3 g, glycerin 10 g, and distilled water 1 L [ 19 ]; (6) Medium 4: sucrose 50 g, glucose 20 g, peptone 60 g, ammonium sulfate 30 g, glycerin 3 g, calcium chloride 3 g, magnesium sulfate 1 g, calcium D-pantothenate 0.6 g, and distilled water 1 L. All the media were sterilized at 121°C in an autoclave sterilizer for 30 min.…”
Section: Methodsmentioning
confidence: 99%